Long-term outcome of thalamic deep brain stimulation in two patients with Tourette syndrome. Issue 10 (26th July 2010) - Ackermans, Linda; Duits, Annelien; Temel, Yasin; Winogrodzka, Ania; Peeters, Frenk; Beuls, Emile A M; Visser-Vandewalle, Veerle
Abstract : Objective: Thalamic deep brain stimulation for intractable Tourette Syndrome was introduced in 1999 by Vandewalle et al . In this follow-up study, the authors report on the long-term (6 and 10 years) outcome in terms of tic reduction, cognition, mood and side effects of medial thalamic deep brain stimulation in two previously described Tourette patients. Methods: The authors compared the outcome of two patients at 6 and 10 years after surgery with their preoperative status and after 8 months and 5 years of treatment, respectively. Standardised video recordings were scored by three independent investigators. Both patients underwent (neuro)psychological assessment at all time points of follow-up. Results: Tic improvement observed at 5 years in patient 1 (90.1%) was maintained at 10 years (92.6%). In patient 2, the tic improvement at 8 months (82%) was slightly decreased at 6 years (78%). During follow-up, case 1 revealed no changes in cognition, but case 2 showed a decrease in verbal fluency and learning which was in line with his subjective reports. Case 2 showed a slight decrease in depression, but overall psychopathology was still high at 6 years after surgery with an increase in anger and aggression together with difficulties in social adaptation. Besides temporary hardware-related complications, no distressing adverse effects were observed. Conclusion: Bilateral thalamic stimulation may provide sustained tic benefit after at least 6 years, but to maximise overall outcome, attention is needed for postoperative psychosocial adaptation, already prior to surgery.